Resistance to Dopamine Agonists in Pituitary Tumors: Molecular Mechanisms - Pivonello, Claudia; Patalano, Roberta; Negri, Mariarosaria; Pirchio, Rosa; Colao, Annamaria; Pivonello, Rosario; Auriemma, Renata Simona (Frontiers in Endocrinology, 2022)
Pituitary neuroendocrine tumours (PitNET) are commonly benign tumours accounting for 10-25% of intracranial tumours. Prolactin-secreting adenomas represent the most predominant type of all PitNET and for this subtype of tumours, the medical therapy relies on the use of dopamine agonists (DAs). DAs yield an excellent therapeutic response in reducing tumour size and hormonal secretion targeting the dopamine receptor type 2 (D2DR) whose higher expression in prolactin-secreting adenomas compared to other PitNET is now well established. Moreover, although DAs therapy does not represent the first-line therapy for other PitNET, off-label use of DAs is considered in PitNET expressing D2DR. Nevertheless, DAs primary or secondary resistance, occurring in a subset of patients, may involve several molecular mechanisms, presently not fully elucidated. Dopamine receptors (DRs) expression is a prerequisite for a proper DA function in PitNET and several molecular events may negatively modify DR membrane expression, through the DRs down-regulation and intracellular trafficking, and DR signal transduction pathway. The current mini-review will summarise the presently known molecular events that underpin the unsuccessful therapy with DAs.